Umgebungskartenschätzung aus Sidescan-Sonardaten für ein autonomes Unterwasserfahrzeug - Woock, Philipp (Karlsruher Schriften zur Anthropomatik / Lehrstuhl für Interaktive Echtzeitsysteme, Karlsruher Institut für Technologie ; Fraunhofer-Inst. für Optronik, Systemtechnik und Bildauswertung IOSB Karlsruhe, 2016)
This work makes several contributions to the process of estimating elevation maps from side-scan sonar data: A new estimation method that recreates sonar measurements by pre-computed known sonar responses (so called kernels) and then derives a height profile from the kernels used. Additionally, a 3D method based on Markov Random Fields and a side-scan sonar simulation environment for arbitraty 3D scenes featuring different sonar modes and several terrain generators have been developed.